دور المعرفة التسويقية في التوجّه نحو الابداع دراسة ميدانية في الشركة العامة لتعبئة المياه /بقين/ - نصور, ريزان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The objective of this study is to determine the role of marketing knowledge in achieving creativity direction at the General Company for Bottling Water (Boukein). This was done by using the descriptive statistical method. A questionnaire was designed with a set of questions related to the studied research variables that were directed to a sample of employees in the studied company. Then, the data was analyzed using the SPSS program. Finally, the study concluded a set of important results, including: - There is a statistically significant effect of the marketing information system on the creative approach at General Company for Bottling Water (Boukein). - There is a significant impact of the management of marketing knowledge on the creative approach at the General Company for Bottling Water (Boukein). - There is a statistically significant impact of customer involvement to create knowledge on the creative approach at the General Company for Bottling Water (Boukein). The researcher also presented a set of suggestions and recommendations that are expected to help the company's employees develop the ways of working at the company. So, the company can have a leading creative center by establishing its marketing efficiency in the Syrian market. تمثل الهدف من هذه الدراسة إلى تحديد دور المعرفة التسويقية في تحقيق التوجه نحو الابداع في الشركة العامة لتعبئة المياه /بقين/ وتم ذلك باستخدام المنهج الوصفي الإحصائي حيث تم تصميم استبيان مؤلف من مجموعة من الأسئلة المتعلقة بمتغيرات البحث المدروسة, والتي تم توجيهها لعينة من العاملين في الشركة المدروسة, ومن ثم تم تحليل البيانات باستخدام برنامج حزمة البرامج الإحصائية الجاهزة للعلوم الاجتماعية SPSS اصدار 2000، ، توصلت الدراسة إلى مجموعة من النتائج كان من أهمها: 1- يوجد تأثير ذو دلالة إحصائية لنظام المعلومات التسويقية على التوجه الابداعي للشركة العامة لتعبئة المياه /بقين/. 2- يوجد تأثير ذو دلالة إحصائية لإدارة المعرفة التسويقية على التوجه الابداعي للشركة العامة لتعبئة المياه /بقين/. 3- يوجد تأثير ذو دلالة إحصائية لإشراك الزبون في خلق المعرفة على التوجه الابداعي للشركة العامة لتعبئة المياه /بقين/. كما قدّمت الباحثة من خلال هذه الدراسة مجموعة من المقترحات والتوصيات التي من المتوقع أن تساعد القائمين على الشركة في تطوير سبل العمل ضمن الشركة للوصول بها إلى مركز ابداعي عال وبالتالي تنافسية شديدة من خلال تثبيت كفاءتها التسويقية في السوق السورية.